Sustainable commercial interiors - Bonda, Penny; Sosnowchik, Katie (Hoboken, New Jersey Wiley, 2014)
"Applying environmentally responsible strategies to the interior design process, Sustainable Commercial Interiors provides designers with everything they need to know about sustainability when working on commercial projects. Organized to mimic the LEED Green Building Rating System, this book covers everything from global environmental issues to water and energy usage to the latest information on materials, finishes, and furnishings. The Second Edition is fully updated to reflect the new LEED 2012 guidelines and includes fifteen brand new case studies that illustrate the green design and building strategies employed in a variety of commercial projects. Illustrated in full color throughout, the new edition includes instructor ancillary materials for classroom use"--
"The Second Edition is fully updated to reflect the new LEED 2012 guidelines and includes fifteen brand new case studies that illustrate the green design and building strategies employed in a variety of commercial projects. Illustrated in full color throughout, the new edition includes instructor ancillary materials for classroom use"--
Machine generated contents note: Foreword Alex Wilson Preface Acknowledgements Introduction Chapter 1 Sustainable Design: Past, Present, And Future Sustainability Defined and Refined Defining "Green" What Is Green Design? Overcoming the Obstacles to Sustainability The Integrated Profession Integrating Sustainability Into Your Design Practice: An Essay by Kendall Wilson What's LEED Got to Do With It? Making Integrated Design Work The Design Charrette Taking the Mystery Out of Commissioning Commissioning the Interior Project: An Essay by Jay Enck Chapter 2 Global Issues: An Overview As the Earth Warms Living Lightly on the Land Wet Gold Want Not, Waste a Lot Healthy Buildings, Healthy People Bio-Inspired Design: What Can We Learn from Nature? An Essay by Judith Heerwagen The Journey Ahead: An Essay by Bill Reed Chapter 3 Sites, Water and Energy Matters of Site Site Sustainability Matters: An Essay by Gina Baker What's LEED Got To Do With It? Reducing Water Use What's LEED Got To Do With It? Optimizing Energy Use Energy Efficiency in an Interiors Project: An Essay by Marcus Sheffer Lighting Heating and Cooling Chapter 4 The Materials Maze Ask More Questions: An Essay by Nadav Malin Navigating the Materials Maze Life Cycle Studies: A Comparison Toxins A Guide to Researching Sustainable Materials: An Essay by Jean Hansen Transparency--or Not Natural Versus Synthetic Materials Furnishings and Finishes: An Overview Fabrics Carpet Resilient Flooring Hard Flooring Wood Flooring Wood and Millwork Furniture Paints, Wall Finishes, and Wallcoverings Surfacing Materials Ceilings Green Product Trends: An Essay by Wanda Lau What's LEED Got To Do With It? Chapter 5 The Indoor Environment The Air That We Breathe Interior Design: First Step Towards Providing Good IAQ: An Essay by Marilyn Black The Elusive Thermal Comfort Noise: The Other Pollutant Let There Be (Day)light Why Daylighting? An Essay by Nancy Clanton The Importance of Views What's LEED Got To Do With It? Chapter 6 The Tools of Our Trade Green Building Organizations, Rating Systems And Design Guides Product Standards and Certifications Multi-Attribute Product Standards and Certifications Single-Attribute Product Standards and Certifications Green Product Information Programs LCA Analysis Tools Product Guides Specifications Four Steps to Greening Your Specifications: An Essay by Ross Speigel The Sustainable Library Chapter 7 The Business Case for Green Design Building a Tangible Symbol Making the Case Costs and Benefits of Green Building The Economics of a Green Work Space: An Essay by Bill Browning An Integrated Whole Chapter 8 Practicing What They Preach What Do Green Professionals Do? An Essay by Holley Henderson Great Expectations U.S. Green Building Council Headquarters, Washington, D.C., USA Dynamic Energy Cannon Design, Chicago, Illinois Repurpose With Style HDR Architecture, Inc., San Francisco, California Engage & Express RTKL Associates Inc., Washington, D.C. The Three C's HOK Chicago, Illinois, USA Adaptive Reuse in Midtown Atlanta Perkins + Will, Atlanta, Georgia, USA Chapter 9 Substance and Style A Bit of Britain in Manhattan BBC Worldwide Americas, New York, NY, USA Respecting the Past, Providing for the Future Federal Center South, 1202 Building, Seattle, Washington, USA The Healing Properties of Nature Fort Belvoir Community Hospital, Fort Belvoir, Virginia, USA High Tech, High Touch King Abdullah University of Science and Technology (KAUST) Academic Library Thuwal, Saudi Arabia True to Its Roots J.W. Marriott San Antonio Hill Country Resort & Spa, San Antonio, Texas, USA Big Impact In a Small Footprint Welch Allyn, Inc., Skaneateles Falls, New York, USA Collaborative Cube Kaleida Health Gates Vascular Institute/SUNY at Buffalo Clinical Translational Research Center, Buffalo, New York Glossary Resources Books TedX Talks Internet Resources
Includes bibliographical references (pages403-408) and index
2
Keywords: ARCHITECTURE / Interior Design / General; Commercial buildings -- Design and construction; Interior architecture -- United States; Office buildings -- United States; Sustainable buildings -- Design and construction; Sustainable design -- United States; Sustainable engineering -- United States